2000
DOI: 10.1016/s0735-1097(00)00534-9
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation lesions: two stents versus one stent—immediate and follow-up results

Abstract: For the treatment of true bifurcation lesions, a complex strategy of stenting both vessels provided no advantage in terms of procedural success and late outcome versus a simpler strategy of stenting only the parent vessel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
155
1
12

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(179 citation statements)
references
References 25 publications
11
155
1
12
Order By: Relevance
“…Long-term (24.4 ± 15.1 months) MACE occurred in about 16% of the total study population, with rates of death and stent thrombosis respectively of 4.7% and 2.7%. Rates of adverse cardiac events are quite variable across literature, reflecting continuous improvement over time, in stenting techniques and devices [1,15,18,[24][25][26][27]. Overall, we experienced a relatively low rate of MACE, and our results are in line with previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…Long-term (24.4 ± 15.1 months) MACE occurred in about 16% of the total study population, with rates of death and stent thrombosis respectively of 4.7% and 2.7%. Rates of adverse cardiac events are quite variable across literature, reflecting continuous improvement over time, in stenting techniques and devices [1,15,18,[24][25][26][27]. Overall, we experienced a relatively low rate of MACE, and our results are in line with previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…Bare metal stent implantation for bifurcation lesions produced higher rates of restenosis and TLR. 5,11 A DES has been proved to significantly reduce restenosis rates compared with a BMS, but it is still comparatively higher at the side branch. 7,12 The results of this study indicated that there was no difference in restenosis rate in the main branch between the 2 groups, but in the side branch it was significantly higher in the 1-DES group than in the 2-DES group.…”
Section: Discussionmentioning
confidence: 99%
“…2 -4 Specifically, the use of bare metal stents (BMSs) for both branches has not improved the results compared with 1-stent plus the kissing balloon technique. 5,6 Recently, several randomized and controlled trials have demonstrated great advantages of drug-eluting stents (DESs) in significantly reducing restenosis and recurrence of symptoms, and improving clinical outcomes after percutaneous coronary intervention (PCI). 7,8 Little is known about the comparative effects of 1-DES plus the kissing balloon technique with the 2-DES for bifurcation angioplasty in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with long sidebranch lesions were systematically excluded from the randomized trials [4]. Registries, though available in greater numbers [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], are of variable quality and use different lesion classification systems, quantitative coronary angiography (QCA) measurements performed in unclear technical conditions, with identical technical strategies bearing different names or different techniques grouped under a single name. Other than the comparison between stent deployment in one versus two branches, a meta-analysis of these various reports has proven quite impossible.…”
Section: Introductionmentioning
confidence: 99%